2006
DOI: 10.1108/09590550610691310
|View full text |Cite
|
Sign up to set email alerts
|

The role of anticipated emotion, desire, and intention in the relationship between image and shopping center visits

Abstract: Purpose -The purpose of this paper is to identify variables that intervene in the relationship between shopping center image and frequency of visits to that shopping center. Variables investigated as intervening are desires, intentions, and positive anticipated emotions. Design/methodology/approach -The method uses a two wave mail survey. One wave gathers intentions and variables antecedent to intentions while a second wave gathers behavioral data. Findings -Findings suggest that desire (i.e. motivation), inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 28 publications
3
86
0
3
Order By: Relevance
“…The critical factor that is associated with patronage behaviour is the loyalty. Different factors influences the loyalty including mall image (Koo, 2003;Hunter, 2006); image and motives (Bellenger et al, 1977;Nevin and Houston, 1980;Finn and Louviere, 1996); convenience, pricing, and quality of shopping centres (Pan and Zinkhan, 2006); mall size and convenience of access (Huff, 1964); atmosphere and friendliness of store people (Bearden, 1977). However, these factors are not uniform across the cultures and regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The critical factor that is associated with patronage behaviour is the loyalty. Different factors influences the loyalty including mall image (Koo, 2003;Hunter, 2006); image and motives (Bellenger et al, 1977;Nevin and Houston, 1980;Finn and Louviere, 1996); convenience, pricing, and quality of shopping centres (Pan and Zinkhan, 2006); mall size and convenience of access (Huff, 1964); atmosphere and friendliness of store people (Bearden, 1977). However, these factors are not uniform across the cultures and regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, in line with research and theory on anticipated emotions and romantic relationship development, as well as the qualitative findings, an individual's expected shopping pleasure with their partner is likely to affect the likelihood of shopping together. This variable receives little attention in shopping research, although Hunter (2006) finds that an individual's positive anticipated emotions intervenes between perceptions of the shopping center's image and her desire to shop at the center. Expected shopping pleasure with a partner is the extent to which an individual positively evaluates the anticipated experience of a specific shopping trip with their partner.…”
Section: Hedonic Motivationsmentioning
confidence: 95%
“…Ajzen (1991Ajzen ( ,2013 and Han and Ryu (2012) asserted that a socio-psychological theory (e.g., TRA, TPB, MGB, Theory of Repurchase Decision-making [TRD]) in essence may be amended by modifying the linkages in the theory and incorporating additional variables that are critical in a particular setting if it can be shown that the theory, including new constructs, captures a greater proportion of the variance in one's intention or behavior after the original theory variables have been taken into account. Such amendment procedures, described as theory broadening and deepening (Perugini & Bagozzi, 2001), have been widely employed in various studies in a variety of contexts (e.g., Bagozzi & Dholakia, 2006;Carrus et al, 2008;Han & Ryu, 2012;Hunter, 2006;Song, Lee, Kang et al, 2012, Song, Lee, Norman et al, 2012Taylor, Ishida, & Wallace, 2009). These researchers generally showed that one of the MGB's theoretical mechanisms is better explained when revising paths to be more appropriate in a particular setting or when involving essential constructs that are important in specific contexts.…”
Section: Model Of Goal-directed Behaviormentioning
confidence: 99%